Using a “Kickoff” to build implementation partner teams and action plans for active implementation of a quality improvement project - Baird, Sean A.; Damush, Teresa M.; Rattray, Nicholas A.; Penney, Lauren S.; Miech, Edward J.; Homoya, Barbara J.; Ferguson, Jared; Myers, Laura J.; Bravata, Dawn M. (Frontiers in Health Services, 2025)
IntroductionA strategy for transitioning implementation successfully from pre-implementation to active implementation is to hold a team “kickoff.” The objectives of this manuscript are: (1) to present the frameworks that guided the development of the Protocol-guided Rapid Evaluation of Veterans Experiencing New Transient neurological symptoms (PREVENT) kickoff strategy, (2) describe design elements of the kickoff and how they contribute to achieving PREVENT kickoff aims; forming teams, developing an action plan, and launching active implementation (3) examine the perceived usefulness of those kickoff design elements toward achieving kickoff aims.MethodsPREVENT was a stepped-wedge trial to improve the quality of Transient Ischemic Attack (TIA) care at six Veterans Affairs (VA) medical centers. The PREVENT kickoff was designed from multiple frameworks: theory of change principles for process improvement; Consolidated Framework for Implementation Research (CFIR); social learning models; and systems redesign. Data collected included pre-kickoff planning documents and post-kickoff debriefs from the PREVENT national team, Audience Response System (ARS) data, post-kickoff site participant evaluations and semi-structured interviews.ResultsSite team participants reflected positively on the framework driven, interactive and interpersonal design elements, team building, and action plan exercises, and found them useful for a successful project launch. In-person and hybrid set-up of the kickoff, interactive elements, and team formation activities emphasized the quality problem, and motivated site implementation providers to plan for stroke/TIA care improvement.ConclusionsImplementation team kickoffs during pre-implementation are a useful approach to inform and engage local clinical teams and to form plans for practice changes to improve clinical care. Clinical Trial Registrationclinicaltrials.gov, identifier NCT02769338.